Provisional Selves: Experimenting with Image and Identity in Professional Adaptation - Ibarra, Herminia (Administrative Science Quarterly, 1999)
This article describes how people adapt to new roles by experimenting with provisional selves that serve as trials for possible but not yet fully elaborated professional identities. Qualitative data collected from professionals in transition to more senior roles reveal that adaptation involves three basic tasks: (1) observing role models to identify potential identities, (2) experimenting with provisional selves, and (3) evaluating experiments against internal standards and external feedback. Choices within tasks are guided by an evolving repertory that includes images about the kind of professional one might become and the styles, skills, attitudes, and routines available to the person for constructing those identities. A conceptual framework is proposed in which individual and situational factors influence adaptation behaviors indirectly by shaping the repertory of possibilities that guides self-construction.